Phenology of Guarea macrophylla Vahl (Meliaceae) in subtropical riparian forest in southern Brazil - Müller,A. (2018)
Abstract Climate is one of the main factors that affect plant behavior. The phenology of Guarea macrophylla Vahl, which is a small tree used for reforestation of degraded areas, was monitored for 18 months in a riparian forest at the Schmidt Stream, Campo Bom, in the state of Rio Grande do Sul, southern Brazil. Vegetative (leaf fall and leaf flushing) and reproductive events were observed, with the latter divided into flowering (flower buds and anthesis) and fruiting (unripe, ripening and ripe fruit). Phenological events were related to temperature, photoperiod and precipitation and their seasonality was verified by circular statistical analysis. Vegetative phenophases were continuous; they were not related to climate factors and presented low intensity, emphasizing the perennial aspect of the species. Flowering occurred during spring and summer. Both flower buds and anthesis were related to temperature and photoperiod. Fruiting was constant and went through all stages of development. Unripe fruits developed during the months with the lowest photoperiod and ripen more intensely in winter, on colder days. Ripe fruit became available for dispersal in spring, in times of longer photoperiod and higher temperatures. Except for leaf fall, all other phenological events showed seasonality in their manifestation. The one-month difference between the onsets of the flowering phases observed in this study indicated that local climate changes induced the early occurrence of this phenophase.